PM3 Based Quantitative Structure Activity Relationship (QSAR) Study on 9-Benzyladenines Derivatives - Singh, P.P.; Singh, Aradhana (Asian Journal of Chemistry, 2010)
With the help of PM3 calculations using Cache software QSAR study has been made on 9-benzyladenines derivatives as adenosine deaminase inhibitors. For QSAR prediction, the 3D modelling and geometry optimization of all the derivatives of 9-benzyladenines have been done with the help of PC Model software using the semi-emperical PM3 Hamiltonian. The MOPAC calculations have been performed with Win MOPAC 7.21 software by applying key words Charge=0, Gnorm-0.1, Bonds, Geo-ok, vector density. The values of descriptors: heat of formation (ΔHf); molecular weight (m.w.); total energy (TE); eigen value of highest occupied molecular orbital (εHOMO); eigen value of lowest unoccupied molecular orbital (εLUMO); absolute hardness (η) and electronegativity (χ), have been evaluated by PM3 methods. The correlation and cross validation coefficient values of the QSAR models are above 0.89 and 0.69, respectively. The combination of descriptors providing the best coefficient values are ΔHf, m.w., TE and εHOMO.